Impact of Low Birth Weight on Early Vascular Aging and Cardiometabolic Phenotypes in Later Life Among Cameroonian Adults - Daniel, Lemogoum; Philippe, van de Borne; Michel, P. Hermans; Danielle, Christiane Kedy Mangamba; Aurel, Sikamo; Elysée, Claude Bika Lele; Marie, Solange Ndom Idejen; Jacques, Doumbe; William, Ngatchou (International Journal of Nutrition, 2020)
Background Evidence suggests that low birth weight (LBW) is associated with increased cardiovascular and metabolic risk in adulthood, including increased arterial stiffness, a marker of early vascular aging (EVA) assessable by pulse wave velocity (PWV), obesity and glucose homeostasis abnormalities. The present study aimed to explore the late impact of LBW on PWV and cardiometabolic phenotypes among young adult Cameroonians. Methods The study evaluated 120 subjects (mean age: 26 ± 5 years; 54% male sex) at the Cameroon Heart Institute, Douala, Cameroon, between January and June 2018. Birth weight (BW) and gestational age, sociodemographic, anthropometrics and fasting capillary blood glucose were recorded in all participants. Blood pressure (BP) and PWV were measured using an automatic oscillometric device (Mobil-O-Graph®). Multiple-adjusted linear regression was used to determine predictive factors for PWV. For assessment of potential impact of BW on EVA, PWV was adjusted for age, sex, body mass index (BMI) and mean arterial pressure (MAP). Results 28 participants (23.3%) of the study sample had LBW (<3000g). There was no gender difference between LBW or normal birth weight patients (NBW; controls). Age- and MAP-adjusted PWV (aPWV) were higher in women with LBW compared to NBW (5.6 m/s and 5.3 m/s respectively, P = 0.038). In men, aPWV was similar in LBW and NBW. In this study population, aPWV was higher (on average +15 cm/s) in LBW than in controls, although the difference was not statistically significant (P=0.083). Multivariate regression analysis showed age, male sex, BMI and MAP were independent determinants of PWV, but not LBW. Compared to NBW controls, the prevalence of overweight/obesity, impaired glucose homeostasis and diabetes was higher in LBW: 42.9% vs 37%; 10.7% vs 3.3%, and 3.6 % vs 1.1%, respectively. Moreover, compared with controls, LBW individuals who were overweight/obese in adulthood had a much higher mean fasting capillary glucose (1.54 ±0.17 g/l vs 0.87 ±0.11 g/l in NBW, p=0.003). Conclusion This study suggests that although LBW is associated with increased aortic stiffness in young adulthood, mainly in women, the association was predominantly driven by aging, MAP, BMI and male sex. In adulthood, LBW subjects exhibited higher obesity indices and altered glucose homeostasis.
Keywords: Birth weight; early vascular aging; glucose homeostasis; pulse wave velocity; overweight/obesity